Corporate Financial Distress and Debt Restructuring: A Systematic Literature Review on PKPU Mechanisms in Indonesia’s Textile Industry - GP Aji Wijaya; Raden Aswin Rahadi (Journal Integration of Management Studies, 2025)
Corporate financial distress is a recurring challenge, particularly during economic downturns and sector-specific crises. In Indonesia, the Penundaan Kewajiban Pembayaran Utang (PKPU) framework offers a legal mechanism to facilitate debt restructuring. This study applies a systematic literature review (SLR) combined with a case study of PT Rejekitex to examine how PKPU mechanisms function within the textile industry. It explores the theoretical foundations of financial distress—including Trade-Off, Agency, and Pecking Order theories—compares PKPU with international frameworks such as U.S. Chapter 11, and identifies key research gaps concerning the long-term effectiveness of PKPU, conflicts among creditors, and recovery strategies adopted by firms. The findings indicate that the success of PKPU-driven restructuring depends on factors such as creditor alignment, industry stability, and firm-specific strategies. The study contributes a conceptual framework that maps the causes, mechanisms, and outcomes of court-supervised restructuring processes under PKPU. While the analysis centres on Indonesia’s textile sector, the proposed framework holds broader relevance for other debt-intensive industries in emerging markets.